PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS DISCOVERY LEARNING PADA MATERI GARIS DAN SUDUT KELAS VII - Rani Martalisa Taorina; Armis '; Maimunah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to produce mathematic learning device in the form of syllabus, lesson plan, and student worksheet based on discovery learning on Lines and Angles topic for 7th grade. The study model used is ADDIE by Dick and Carry that consist of analyze, design, development, implementation, and evaluation. Development process is done until the development stage. The research instrument used is validity instrument and practicality instrument. The validity instrument is a validation sheet to assess the feasibility of syllabus, lesson plans and student worksheet. The practicality instrument is in the form of observation sheet of learning process implementation and questionnaire of student response . Learning device developed are validated by four validators. The research trials were conducted in SMP Negeri 13 Pekanbaru which is tested in a small group and large group. Small group trial aims to assess the practicability based on student response questionnaire, while the large group to assess the practicability based on the observation sheet of learning process implementation and student response questionnaire. Based on the data analysis, it can be conclude that the average value for syllabus is 3.42 in very valid category which means that syllabus is feasible to be used; as well as the average value for lesson plan and student worksheet are 3.71 and 3.71. That are in very valid category which means that lesson plan and student worksheet are feasible to be tested. The student worksheet valued as very practical with mean score for small group and large group testing are 3,67 and 3,38. The lesson plan also valued as very practical with mean percentage is 96,67%. These categories mean that the lesson plan and student worksheet are feasible to used in school.Keyword: Mathematics Learning Device, Discovery Learning, Development Research, ADDIE Model